Human Capital Misallocation and Output per Worker Differences: Beyond Cobb-Douglas - Jan Trenczek; Konstantin M. Wacker (Global Labor Organization (GLO), 2023)
Misallocation of human capital across sectors can have substantial negative implications for aggregate output. So far, the literature examining this type of labor misallocation has assumed a Cobb-Douglas production function. Our paper departs from this assumption and instead considers more exible CES production functions with different labor skill types as individual inputs. Our estimates from sectoral data of 39 countries suggest that physical and human capital are less substitutable than Cobb-Douglas assumes. Our counterfactual results indicate that human capital misallocation can explain approximately 15% of output per worker variation across countries, which is substantially less than under a Cobb-Douglas specification (21%).
Keywords: O41; O47; E24; 330; Misallocation; Human Capital; Sector level; Production function; Elasticity of substitution; Total factor productivity